Snowbush spanworm (larva), white-tipped black (adult), Melanchroia chephise (Stoll) (Insecta: Lepidoptera; Geometridae: Melanchroia): EENY812/IN1427, 5/2024 - McCormick, Kaydie; Dale, Adam (EDIS, 2024)
Melanchroia chephise, commonly known as the snowbush spanworm or white-tipped black, is an occasional insect pest of snowbush shrubs and several other ornamental plant species. Found throughout the southern United States, these gregarious moth caterpillars can commonly be found defoliating their chosen hosts soon after they emerge en masse. The colorful appearance of the caterpillars may be alarming, but they pose little risk to people, and usually offer no lasting harm to the plants they feed on. The adult moths, with their black and white wings, can be an attractive addition to a pollinator garden. This publication describes how to identify this insect and provides in-depth information on its biology, development, and management.